PENERAPAN COMPUTER ASSISTED INSTRUCTION (CAI) DALAM PEMBELAJARAN PENGUCAPAN KOSAKATA BAHASA NIAS BERBASIS WEB - BUGIS, ERMINSYAH (STMIK Kaputama, 2019)
Computers as part of the development of technology have been used in various aspects including advocating, implementing educational evaluation processes as part of a culture of the means to transmit values and ideas where everyone is able to play a role in transforming values for the progress of the nation and state. One technology that is developing quite rapidly in the world of education is Web technology that is utilized for learning applications. Many Nias people do not understand Nias language, especially in terms of pronunciation of the Nias language vocabulary that does have its own uniqueness. The Nias language recognizes 22 alphabets, which are 6 vowels A, E, I, O, U and are added with Ö (read as